IMPACT OF CAREER INTERVENTION ON VOCATIONAL PREFERENCE AMONG SECONDARY SCHOOL STUDENTS OF NIGERIA: A COMPARATIVE STUDY - Usman Isah; Syed Mohamad Syed Abdullah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This comparative study aimed to assess the impact of career intervention on the vocational preference of secondary school students in the Hadejia Emirate of Jigawa State Nigeria. The research objectives included examining the effects of career intervention on vocational preference before and after the intervention, exploring gender differences in the intervention’s impact, and investigating variations in the intervention’s effect among students in different academic fields. A quasi-experimental design was employed, involving a pre-test post-test control group approach. Twelve secondary schools were randomly selected from the Hadejia, Kafin Hausa, and Birniwa education zones, with a sample size of 240 students evenly distributed between male and female participants. The research instrument, the Students’ Vocational Preference Scale (SVPS), consisted of demographic information and statements related to vocational preference. The SVPS utilized a five-point Likert scale, and its validity and reliability were established through expert review and test-retest procedures. Statistical analysis involved paired-sample t-tests, independent sample t-tests, and analysis of variance (ANOVA). The study’s findings indicated a significant difference in the effect of career intervention on vocational preference, suggesting a positive impact on students’ vocational preferences. However, the intervention’s effect did not significantly differ among students in commercial, arts, and science fields. Career intervention was not Gender sensitive. The study contributes to the understanding of the effectiveness of career interventions for secondary school students in Nigeria, emphasizing the importance of providing guidance and support to facilitate informed career decision-making.